Tourism Policy Based on Good Tourism Governance in Realizing Sustainable Tourism in the Lake Toba Tourism Area, North Sumatera - Hajar, Siti; Wahyudi, Heri; Ambia Arma, Nur; Kholik, Kholilul (Iapa Proceedings Conference, 2024)
This study aims to analyze and formulate tourism policies based on Good Tourism Governance (GTG) in realizing sustainable tourism in the Lake Toba Tourism Area. As one of the super priority destinations in Indonesia, the development of Lake Toba faces challenges related to environmental conservation, improving the welfare of local communities, and managing sustainable tourist attractions. This study is a survey study which is then analyzed using SEM based on variants or PLS-Path Modeling. The results of the study indicate that the implementation of GTG principles, such as community participation, transparency, accountability, and partnerships between stakeholders, plays a significant role in creating sustainable tourism. An effective policy model in the Lake Toba Area involves synergy between the government, local communities, and the private sector in maintaining a balance between economic, social, and environmental aspects. The development of this GTG-based policy is expected to maximize the tourism potential of Lake Toba while maintaining the sustainability of natural resources and strengthening the capacity of local communities.